Changing Trends in Adult and Continuing Education: The Ghanaian Experience - Oheneba-Sakyi, Y.; Kwapong, O.A.T.F.; Badu-Nyarko, S.K.; Tagoe, M.A. (Changing Perspectives on the Social Sciences in Ghana, 2014)
Using archival materials, scientific investigation, secondary data, and field reports and observations, this chapter provides a critical review of the history of Adult and Continuing Education in Ghana, highlighting the global efforts that shaped adult and continuing education in the country. The chapter questions the continuous confusion associated with the concept of adult education by examining the various meanings attached to it as an academic discipline. Finally, there is a discussion of the expansion of educational delivery at the university to include distance education and e-learning in the activities of the Institute of Continuing and Distance Education and the way forward in terms of relevance and practice.
Keywords: Adult and continuing education; Ghana; Colonial influence; Philosophy of adult education Adult education research